Elaboración de un Prototipo para la Fabricación de Ecopostes con Plástico (PET) en el Relleno Sanitario Romerillos del Cantón Mejía. - Torres Caiza, Luis Fernando (2017)
The present research was carried out in the Recycling Plant of the Center for Treatment and Final Disposal of Solid Waste “Romerillos” from Mejia Canton with the purpose of elaborating a prototype from plastic Polyethylene Terephthalate (PET) for the manufacture of Ecopostes, through the tabs and controls of weight was determined the amount of plastic material existing in the landfill, the types of (PET) existing was charaterized using the direct observation of the waste in the recycling center with the help of the association of recyclers can be obtained different types plastics that can be reused as plastic (PET) for the elaboration of a prototype of Ecopostes. Being the (PET) N ° 1 with the components of a density of 0.6 g / cm3, the density is an important property when finding properties in a material, being the one of better handling at the moment of entering to boil only needs of hot. Therefore for the design of the mold for an ecoposte was realized with a diameter of 2m and 0.10mxL. In addition a socialization was carried out with the Partners of the Social Development Association Romerillos (recyclers), this way it will be possible to give technical talks on the use and benefits of the product, consequently the project is based on the reduction of the emissions of gases of effect Greenhouse, saving of raw material, natural resources, energy and economic.